Sex difference in soccer instep kicking - Iitake, T.; Hioki, M.; Takahashi, H.; Nunome, H. (Journal of Sports Sciences, 2023)
We aimed to clarify the differences in soccer instep kicking dynamics between sex groups. The instep kicking of seven female (height: 160.3 ± 6.1 cm; mass: 54.3 ± 5.2 kg) and seven male (height: 173.0 ± 5.9 cm; mass: 70.0 ± 9.0 kg) players were recorded by a motion capture system (500 Hz). Joint moments of the kicking leg were computed and normalized by the body mass and height. Statistical parametric mapping was used to compare the entire kicking motion between the two groups. Significantly slower resultant ball velocity seen in female players was most likely explained by their significantly slower run-up velocity, shorter leg length and lower foot-ball velocity ratio. Female players exhibited significantly smaller knee joint moment in the latter part (80-86%) of kicking. Also, significantly smaller positive work done by knee extension moment and the ratio of work (knee extension/hip flexion) were found in female players. These results suggested that the suppressed knee extension moment action was identified as a key kinetic characteristic in the instep kicking of female players, and to compensate for this action, they more rely on the work due to hip flexion moment to execute the instep kicking.